2015
DOI: 10.1002/jmv.24324
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of VP1 gene of coxsackievirus A16 prevalent among hand foot mouth disease suffered children in Taizhou, P. R. China, between 2010 and 2013

Abstract: A total of 453 strains of Coxsackievirus A16 (CV-A16) were screened out of 1,509 hand-foot-mouth disease (HFMD) samples collected in Taizhou during the period from 2010 to 2013. And between first quarter of 2011 and first quarter of 2013, an outbreak of CV-A16 was found among the HFMD sufferers in Taizhou. Phylogenic analysis of VP1 sequences indicated a major CV-A16 sub-group in Taizhou, whose change pattern of effective population sizes was found to be similar to the pattern of the actual percentage changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…And because N31D mutation is a synapomorphy of TZ1‐1, we further conclude the outbreak might be correlated with the occurrence of N31D mutation. In previous studies [Zha and Ma, ; Ma and Zha, ], we consistently found the outbreaks of Coxsackievirus‐A6 (CV‐A6) and Coxsackievirus‐A16 (CV‐A16) associated with respective mutations at their VP1‐caspid sites, which is similar to the conclusions drawn in this study. We suggest that the conclusive similarities reached in these three different studies should not be considered merely coincidental, but that these mutations should be assumed to be correlated with epidemiological outbreaks.…”
Section: Discussionsupporting
confidence: 91%
“…And because N31D mutation is a synapomorphy of TZ1‐1, we further conclude the outbreak might be correlated with the occurrence of N31D mutation. In previous studies [Zha and Ma, ; Ma and Zha, ], we consistently found the outbreaks of Coxsackievirus‐A6 (CV‐A6) and Coxsackievirus‐A16 (CV‐A16) associated with respective mutations at their VP1‐caspid sites, which is similar to the conclusions drawn in this study. We suggest that the conclusive similarities reached in these three different studies should not be considered merely coincidental, but that these mutations should be assumed to be correlated with epidemiological outbreaks.…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of CVA16 in Beijing was related to the spread of cluster 3 of clade B1b from 2014 to 2019, all of which had L23M mutation. This mutation was also found in an outbreak of CVA16 in Taizhou from 2011 to 2013 [47]. Whether it is beneficial for virus transmission remains to be analyzed in depth.…”
Section: Discussionmentioning
confidence: 88%
“…In 2008, HFMD was classified as a class C infectious disease in mainland China [3,20]. The frequent recombination and mutation of virus genes has led to HFMD outbreaks associated with CVA16 presenting with different symptoms in different regions [6,21]. There is currently no CVA16 antiviral treatment available.…”
Section: Introductionmentioning
confidence: 99%